Assessment of adaptation capabilities of the cardiovascular system of schoolchildren living near the Chornobyl Exclusion Zone (Environment & Health, 2023)
purpose of the study is to study the adaptive capabilities of the cardiovascular system of schoolchildren living near the Chornobyl Exclusion Zone.Research methods. Anthropometric, instrumental, mathematical and statistical.Results. The study covered 1139 schoolchildren aged 6-17 years (579 boys, 560 girls) who live in rural settlements of Ivankivskyi and Polisskyi districts located near the Chornobyl Exclusion Zone. The survey included the determination of the specific activity of 137Cs (Bq/kg) in the body of children, followed by the calculation of the median and interquartile range in the analyzed groups; physical performance of schoolchildren with the definition of the Ruffier index; assessment of the level of functioning of the cardiovascular system and its adaptive potential. Most of the examined children showed tension and poor adaptation of the cardiovascular system. Disruption of adaptation mechanisms in schoolchildren was recorded in 17.38 % of cases, while in the group of girls with increased body weight it was determined significantly more often than in the group of boys. The reason for this situation, taking into account the genetic characteristics and specific activity of 137Cs in the body, may be hypodynamia. Satisfactory adaptation, as an indicator of health and stable balance of all systems of the child's body, was determined only at the level of 5-7 %. It was concluded that it is necessary to constantly monitor the adaptive capabilities of the cardiovascular system in schoolchildren living near the Chornobyl Exclusion Zone in order to prevent the development of serious diseases in them in the future. When assessing physical development and the state of the cardiovascular system, it is also necessary to take into account the level of incorporated radionuclides and the state of the genetic apparatus of the folate cycle.